O uso de jogos eletrônicos no ensino de conceitos básicos de inovação: compreendendo o uso da tecnologia - Moura, Fernando Turíbio de (Universidade Federal do Tocantins, 2021)
Introduction - Electronic games are the object of great human and cultural fascination, causing significant impacts on society and contributing to impactful innovations in the way they are used. Objective - To understand the history of electronic games and their relationship with technological innovation and computational technologies, to study their feasibility and impact with the creation of a game prototype around innovation. Methodology - Investigative research with exhaustive bibliographic deepening of the history of electronic games and most impactful innovations. Deductive and exploratory, producing from the acquired knowledge a prototype of an electronic game around innovation with application and data collection. Results - The IDEABREAKER game prototype was created, which deals with basic concepts of innovation where an audience of 200 people tested the application with significant engagement results. 51% of users played more than once, 96.5% played at least once and the average playing time was 15% longer than the control average. Conclusions - Electronic games are a potential tool for use around innovation and for the dissemination of related knowledge in a productive way and with a high potential for engagement.